2016
DOI: 10.1186/s12913-016-1352-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of multiple sclerosis in Brazil: a cross-sectional multicenter study

Abstract: BackgroundMultiple sclerosis (MS) is a central nervous system disease associated with irreversible progression of disability, which imposes a substantial socioeconomic onus. The objective of this study was to determine the economic impact of multiple sclerosis from the Brazilian household and healthcare system perspectives. Secondary objectives were to assess the impact of fatigue on daily living and health-related quality of life (HRQL) of MS patients.MethodsThis is a cross-sectional study in which Brazilian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 35 publications
2
37
1
2
Order By: Relevance
“…For living situation in this study, the majority of MS patients lived with family. This finding is coherent with [26] who confirmed that 94 % of MS patients were living with family/spouse. While [25] mentioned that about half of the patients were living with families.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For living situation in this study, the majority of MS patients lived with family. This finding is coherent with [26] who confirmed that 94 % of MS patients were living with family/spouse. While [25] mentioned that about half of the patients were living with families.…”
Section: Discussionsupporting
confidence: 90%
“…According to level of education, it shows that more than half of MS patients had a secondary level and less than half with bachelor level, this agreed with [25] who reported that 78% had diploma degree and below this level of literacy. In addition [26] reported that (41%) had high school level of education.…”
Section: Discussionmentioning
confidence: 99%
“…The costs to the patients and their families, USD 24,121 annually and USD 1,575,200 lifetime, were specified. Later, studies on the cost of MS to the patients and their families have concentrated on direct [9][10][11] or indirect [12][13][14] costs. None of the above studies, except for the United Kingdom study from 1994, included income tax effects.…”
Section: Introductionmentioning
confidence: 99%
“…Information on the cost of the disease in Latin America is very limited, most studies having been performed in Brazil, Colombia and Argentina [ 5 , 27 , 28 ]. In Brazil, the annual direct cost was estimated at 19,012.32 USD (SD: 10,465.96), with no significant differences identified according to the patient’s disability [Expanded Disability Status Scale (EDSS) in mild (0–3), moderate (4–6.5) and severe MS (≥7)] [ 28 ]. In Colombia, differences were detected according to the patient’s disability, with the total cost, from the perspective of the third-party payers, for a patient EDSS 3–5.5 of 25,713 USD, and for a patient with EDSS 8–9.5 of 10,543 USD [ 29 ].…”
Section: Introductionmentioning
confidence: 99%